A 3D Lithiophilic Mo2 N-Modified Carbon Nanofiber Architecture for Dendrite-Free Lithium-Metal Anodes in a Full Cell - Luo, Liu (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.